Proposition of critical levels and nutrient sufficiency ranges in leaves of 'White Moscato' (Vitis vinifera 'Muscat') and 'Bordeaux' (Vitis labrusca 'Ives') - Ayres, Gustavo (2023)
The Compositional Nutrients Diagnosis (CND) can establish indexes that establish deficiency, normality or excess, and even critical levels (CL) or sufficiency ranges (SR) in grapevine leaves. However, this information is scarce in 'White Moscato' and 'Bordeaux' cultivars cultivated in subtropical regions of the world. The study aimed to propose the CND, CL and SR indexes of nutrients in leaves of 'Bordeaux' and 'White Moscato' grapevine cultivars, cultivated in subtropical conditions. Leaves were collected from 105 'White Moscato' and 'Bordeaux' vineyards. Leaves were prepared, dried, ground and subjected to chemical nutrient analysis. Productivity was evaluated. The nutritional status of the grapevine was calculated using the CND method. The CND-r2 indexes were effective in establishing the nutritional status of 'White Moscato' and 'Bordeaux' grapevines, in relation to the concentration of nutrients in leaves of N, P, K, Ca, Mg, B, Cu, Fe, Mn and Zn in deficient, adequate and excessive concentrations. The application of the CND method in the grapevine database showed lower SRs for macronutrients N, K, Ca, Mg and S, and the breadth of the nutritional range for nutrients N, K, Mg, and Fe was smaller than reported in literature. The CND methodology established the critical level and nutrient sufficiency ranges suitable under current grapevine production conditions. Multi-nutrient combinations were more effective than the analysis of a single nutrient in expressing that the limitation of a certain element can reduce the productivity of the grapevines.